A rendszerhasználati komponens a villamos energia árában - Závecz, Ágnes (Acta Scientiarum Socialium, 2015)
The current paper analyses the attributes and historic trends of a special price, paid for the usage of the network that – as part of the basic infrastructure – makes electric power available. Network usage fees represent a component of power’s total end-user price. The research timeline lasted from the restructuring of the state-owned Hungarian electricity industry into joint-stock companies at the beginning of the 90s, to 2013. Within this period the focus has been on the market liberalization period starting with 2003. Key reason for this is that data availability is problematic for a longer period, especially regarding price-component data sets, while the total price’s internal structure and the content of available statistical data have changed several times. In this paper I have examined all components of the price with a special emphasis on the network usage element. Fees to be paid for network services comprise of tariffs related to system operation, the transmission grid and the distribution network. As network services are considered by both economic literature and policy makers to be naturally monopolistic, these tariffs are regulated and not subject to market liberalization. Changes in pricing have been determined by two major cycles: (1) the overall principles of the market model during the stages of public utility, dual market and liberalised competitive market; and (2) the detailed price regulation via a series of four-year long cycles. The price regulation methodology ensured from a theoretic aspect a balanced development of network tariffs. In the third part, the article presents a calculation of the average yearly per unit network usage prices and finally an evaluation of the relationship between the total end-user price and the network component.